Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1600-0714.2007.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinico‐pathologic correlations of myofibroblastic tumors of the oral cavity. II. Myofibroma and myofibromatosis of the oral soft tissues

Abstract: Myofibroma should be included in the clinical differential diagnosis of masses of the oral soft tissues, especially in the tongue and buccal mucosa of children and adolescents. Histological differential diagnosis includes benign and malignant spindle-shaped lesions. Treatment of choice is local excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
77
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 44 publications
7
77
0
4
Order By: Relevance
“…It also tends to affect patients at a mean of 31.2 years of age [10]. Oral myofibroma, which may also occur in adults, commonly affects infants [11]. Oral lipomas, which frequently appear with a yellowish tinge and a soft consistency, predominantly affect the buccal mucosa and are more common in patients between 40 and 60 years of age [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also tends to affect patients at a mean of 31.2 years of age [10]. Oral myofibroma, which may also occur in adults, commonly affects infants [11]. Oral lipomas, which frequently appear with a yellowish tinge and a soft consistency, predominantly affect the buccal mucosa and are more common in patients between 40 and 60 years of age [12].…”
Section: Discussionmentioning
confidence: 99%
“…Schwannoma, neurofibroma, myofibroma, and lipoma consist of smooth-surfaced, slow-growing, asymptomatic masses of variable size [9][10][11][12], representing the clinical feature of the current case. The peak of incidence in schwannoma commonly occurs between the third and sixth decades of life and tends to show a predilection for the palate [9].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 However, this pattern is not evident with oral lesions, where myofibromas are considered rare tumours. 3 Interestingly, the epidemiology is reversed, with a female prevalence and oral lesions appearing within the first two decades.…”
Section: Discussionmentioning
confidence: 98%
“…1,2 The solitary myofibroma presents usually in either the skin or subcutaneous tissues of the head, neck, trunk or skeletal muscles. Relatively few involve bone, commonly the skull, whereas the multicentric form typically involves bone and soft tissue, with frequent occurrence in visceral locations.…”
mentioning
confidence: 99%
“…The authors reviewed 307 nonodontogenic spindle cell neoplasms accessioned over a 20-year period from an oral pathology service and observed that only 8 cases were diagnosed as myofibroma. In a recent review of English language literature, Vered et al (6) found only 41 cases of oral soft tissue myofibroma. Typically, this lesion is seen in neonates and infants with few cases reported in adults patients.…”
Section: Discussionmentioning
confidence: 99%